EVOLUTION OF MASS COMMUNICATION: AN OVERVIEW OF NEW MEDIA - Adelabu, Omowale T.; Oyegoke, Nathaniel Adeoye; Adesoji, Ademola Adewale; Ojewumi, Oluwaranti Olufunke; Dada, Abdulateef (African Journal of Social and Behavioural Sciences, 2024)
This paper explores the characteristics and implications of new media, including the internet, social media, mobile technologies, and digital platforms, in democratizing access to information, fostering global connectivity, and enabling user-generated content and participatory culture. Drawing on theoretical frameworks from communication studies, sociology, and media psychology, the paper analyses the societal and cultural implications of new media on individuals, communities, and institutions. It explores the transformative effects of new media on communication practices, social interactions, political participation, and ownership of cultural production, as well as its influence on power dynamics, media, and regulatory frameworks.